AMBITION FOR FAME IN DARREN ARONOFSKY'S BLACK SWAN MOVIE: A PSYCHOANALYTIC APPROACH - Amelia Wahyu Anggraini Putri; Nugroho, Abdillah (Universitas Negeri Surabaya, 2024)
This study aims to identify the indicators of ambition for fame, how ambition is reflected, and why ambition for fame is reflected in Black Swan, a movie directed by Darren Aronofsky. The analysis of the ambition for fame in Darren Aronofsky's Black Swan movie is the research problem. The descriptive qualitative method was used in this research. To analyze the data, the researcher used Sigmund Freud's Psychoanalytic Theory. The data was collected by taking notes and doing library research. The theory posits three fundamental concepts: the Id, Ego, and Superego. The result shows that Nina Sayer's id is subconsciously driven by a deep desire for perfection in the ballet world and her ambition to become a swan queen. The Ego can be seen in Nina, who tries to fulfill her strong desires with many demands from her mother. The Superego can be seen in that Nina is under pressure from her mom, so she feels depressed. So it can be concluded that the ambition for fame in Black Swan movie can be reflected in Sigmund Freud's Psychoanalytic Theory.